HISTOLOGICAL STRUCTURE OF LYMPHOCYTES, MONOCYTES IN DOGS WITH DERMATITIS PRE AND POST THERAPY - Made Ananda Giri Tanaya; Ni Ketut Suwiti; I Nyoman Suartha; Sri Kayati Widyastuti; Ni Luh Eka Setiasih; I Made Kardena (Buletin Veteriner Udayana, 2025)
A study was conducted to analyse the histological structure of lymphocytes and monocytes in dogs with dermatitis before and after therapy. Dermatitis is skin inflammation that can be caused by bacterial infections, allergies, or environmental factors. This study used 20 dogs with dermatitis that were given a combination of antiparasitic, antibiotic, anti-inflammatory, and antihistamine therapy. Blood samples were taken before and after therapy to be analysed using Morphology of Edge Blood (MDT) staining to observe changes in the histological structure of lymphocyte and monocyte cells. The results showed: before therapy, lymphocytes and monocytes experienced more necrosis (P<0.05) histological structure changes such as pycnosis, karyorexis, and karyolysis. After therapy, there was a decrease in the number of cells that experienced necrosis in lymphocytes, from 8.45 ± 2.08% to 6.85 ± 1.75%. Whereas in monocytes, there was a decrease in the number (P<0.05) of necrotised cells at post- therapy, from 27.5±19.4% to 13.5±10.3%. The conclusion of this study is that the histological structure of lymphocytes and monocytes that experience necrosis is less than cells that do not necrose. The histological structure of the cells showed a lot more normal. The combination therapy used proved effective in improving the structure of lymphocytes and monocytes.